Ahmed Yesevî’de Ölüm Algısı / Ahmad Yasawi’s Perception of Death - KIZILER, Hamdi (Journal of History Culture and Art Research, 2016)
Abstract Death comes to all living creatures. Therefore, humans have always wondered about the phenomenon of death which ends the mortal life and assigned meanings to it. As there were some who assumed the death evil and scary, others thought it was blessed and greeted it happily. Without any doubt, this second group mainly consisted of Sufi people. They do not assume death as an annihilation but a phenomenon that lets them reunite with Allah The Almighty, who we owe our existence. In 12th century’s Central Asia, Sufi Ahmad Yasawi also greeted the death with happiness and perceived it as something that leads him to The Lord. According to him, the soul which forms the main essence of the human does not die, but only the body does. This is simply the transformation of human from one form to another. Thus death is not an annihilation but it is actually the human’s blissful reunion with Allah. This study handles with the Ahmad Yasawi’s perception of death and the meanings he assigned to in the context of his masterpiece, Diwan al-Hikmah. Öz Bütün canlılar mutlaka bir gün ölecektir. Bu sebeple insanoğlu, ölüm gibi dünya hayatını sonlandıran bir olguyu merak etmiş ve ona çeşitli anlamlar yüklemiştir. Ölümü kötü algılayan ve dolayısıyla ona korkarak yaklaşanlar olduğu gibi, onu iyi gören ve sevinçle karşılayanlar da olmuştur. Şüphesiz bu ikinci zümrenin başında sufiler gelir. Onlar ölümü bir yok oluş olarak değil, varlığımızı borçlu olduğumuz Yüce Allah’a kavuşturan bir olgu olarak görmüştür. Orta Asya’da XII. yüzyılda yaşamış ünlü ve etkili sufi Ahmed Yesevî de ölümü sevinçle karşılamış, kendisini Rabbine götüren bir sebep olarak algılamıştır. Ona göre insanın asıl özünü teşkil eden ruh ölmez, sadece beden ölür. Bu da insanın bir halden başka bir hale dönüşmesinden başka bir şey değildir. O zaman ölüm hiçbir zaman yok oluş değil, hakikatte insanın sevgiliye (Allah’a) kavuşmasıdır. Bu çalışmada Ahmed Yesevî’nin Divan-ı Hikmet’i esas alınarak onun ölüm algısı ve ona yüklediği anlamlar ele alınmıştır.